Loess record of the Pleistocene-Holocene transition on the northern and central Great Plains, USA - Mason, Joseph A.; Miao, Xiaodong; Hanson, Paul R.; Johnson, William C.; Jacobs, Peter M.; Goble, Ronald J. (Quaternary Science Reviews, 2008)
Various lines of evidence support conflicting interpretations of the timing, abruptness. and nature of climate change in the Great Plains during the Pleistocene-Holocene transition. Loess deposits and paleosols on both the central and northern Great Plains provide a valuable record that can help address these issues. A synthesis of new and previously reported optical and radiocarbon ages indicates that the Brady Soil, which marks the boundary between late Pleistocene Peoria Loess and Holocene Bignell Loess, began forming after a reduction in the rate of Peoria Loess accumulation that most likely occurred between 13.5 and 15 cal ka. Brady Soil formation spanned all or part of the Bolling-Allerod episode (approximately 14.7-12.9 cal ka) and all of the Younger Dryas episode (12.9-11.5 cal ka) and extended at least 1000 years beyond the end of the Younger Dryas. The Brady Soil was buried by Bignell Loess sedimentation beginning around 10.5-9 cal ka, and continuing episodically through the Holocene. Evidence for a brief increase in loess influx during the Younger Dryas is noteworthy but very limited. Most late Quaternary loess accumulation in the central Great Plains was nonglacigenic and was under relatively direct climatic control. Thus, Brady Soil formation records climatic conditions that minimized eolian activity and allowed effective pedogenesis, probably through relatively high effective moisture. Optical dating of loess in North Dakota supports correlation of the Leonard Paleosol on the northern Great Plains with the Brady Soil. Thick loess in North Dakota was primarily derived from the Missouri River floodplain; thus, its stratigraphy may in part reflect glacial influence on the Missouri River. Nonetheless, the persistence of minimal loess accumulation and soil formation until 10 cal ka at our North Dakota study site is best explained by a prolonged interval of high effective moisture correlative with the conditions that favored Brady Soil formation. Burial of both the Brady Soil and the Leonard Paleosol by renewed loess influx probably represents eolian system response that occurred when gradual change toward a drier climate eventually crossed the threshold for eolian activity. Overall, the loess-paleosol sequences of the central and northern Great Plains record a broad peak of high effective moisture across the late Pleistocene to Holocene boundary, rather than well-defined climatic episodes corresponding to the Bolling-Allerod and Younger Dryas episodes in the North Atlantic region. (C) 2008 Elsevier Ltd. All rights reserved.
id: 1993; PT: J; UT: WOS:000260545800008